Rutin-loaded polymersomes and ethosomes: ex vivo establishment of cutaneous penetration and antilipoperoxidative activity - Ariede, Maíra Bueno (2024)
The production of free radicals by the human body leads to various harmful effects, including skin aging. In the cosmetic field, several studies aim to counteract these deleterious effects through the use of antioxidant substances. However, many of these molecules have properties that hinder their penetration into the skin. Rutin is known for its high antioxidant activity, but it cannot penetrate the deeper layers of the skin without a carrier to promote its penetration/permeation. Different nanocarriers, such as niosomes, polymersomes, liposomes, and ethosomes, are used to facilitate the transport of molecules that have difficulty crossing the epidermal barrier. These carriers have structural differences that may contribute differently to the transport of molecules to deeper skin layers. In this research, rutin was encapsulated/associated with ethosomes and polymersomes, and its penetration in/across the stratum corneum and antilipoperoxidative action were established ex vivo in participants. The nanoparticles were analyzed for particle size, zeta potential, and rutin encapsulation rate. The different nanocarriers were incorporated into a gel vehicle to evaluate antioxidant efficacy ex vivo. The ethosome and polymersome vesicles associated with rutin showed appropriate parameters for nanoscale vesicles, with encapsulation capacities of 74.34% and 83.45%, respectively. However, ex vivo tests revealed that both structures did not exhibit satisfactory profiles for enhancing the active compound\'s penetration across the participants\' stratum corneum and antioxidant capacity. This behavior may be attributed to possible protocol interferences or modifications in vesicle development and even the rutin concentration in the gel. Adjustments in these areas could likely provide different results for the topical delivery of rutin.